Occurrence of blaNDM Variants Among Enterobacteriaceae From a Neonatal Intensive Care Unit in a Northern India Hospital - Ahmad, Nayeem; Khalid, Shamsi; Ali, Syed M.; Khan, Asad U. (Frontiers in Microbiology, 2018)
Carbapenem-resistance among enterobacteriaceae has become a global health concern. The objective of this study was to understand NDM producing enterobacteriaceae and their genetic basis of resistance, spreading in neonatal intensive care unit. Carbapenem resistant NDM producing enterobacteriaceae isolates were recovered from rectal swab and blood sample of infants admitted in NICU. These were determined by using Carba-NP test. All isolates were identified using BD PhoenixTM-100 and MICs were determined by broth microdilution method. The blaNDM and associated resistant markers were checked by PCR followed by sequencing. Moreover, ERIC-PCR and genetic environment of blaNDM gene were also performed for the analysis of clonal relationship and genetic surrounding of the strains. We characterized 44 isolates with blaNDM variants in Escherichia coli (45.5%), Klebsiella pneumoniae (40.9%), Citrobacter freundii (4.5%), Citrobacter braakii (2.3%), Klebsiella oxytoca (2.3%), Enterobacter cloacae (2.3%), Enterobacter aerogenes (2.2%) from NICU, showing resistance against all antibiotics except colistin and polymixin B. ISAba125 and bleomycin gene were found surrounding all blaNDM variants, besides class I integron on plasmid. (ERIC)-PCR data revealed non-clonal relatedness among most of the isolates. The transfer of resistant markers was confirmed by conjugation experiment. The PCR-based replicon typing was carried out using DNA of transconjugants. These isolates carried NDM-1 (20.45%), NDM-4 (36.36%), NDM-5 (38.64%), NDM-7 (4.55%), along with OXA, CMY and SHV variants on conjugative plasmid of IncFIA, IncFIC, IncF, IncK, IncFIB, IncB/O, IncHI1, IncP, IncY, IncFIIA, IncI1 and IncN types. An increased number of carbapenem-resistant NDM producing enterobacteriaceae isolates recovered from NICU which is alarming signal for health workers and policy makers. Hence, it is utmost important to think about infection control measures.